Cultural, Morphological And Biochemical Variations Among Different Isolates Of Xanthomonas Axonopodis Pv. Malvacearum (Journal of Plant Disease Sciences, 2023)
On NA media, the cultural and morphological characteristics and variability of Xanthomonas axonopodis pv. malvacearum were studied, including colony colour and shape, colony size, cell shape, appearance, colony margin elevation, and texture. The bacterium was an aerobic, motile, gram-negative rod with a single polar flagellum. Pathogen colonies varied in size from small to medium, circular, convex, slightly to highly raised and mucoid, light yellow to dark yellow on NA media. The biochemical characteristics of X. axonopodis pv. malvacearum revealed positive responses for potassium hydroxide (KOH) solubility, starch hydrolysis, gelatine liquefication, H2S production, Catalase test, and tolerance to 5% NaCl, but negative responses for indole production and methyl red test.
Keywords: Biochemical; Cotton; Variation; Xanthomonas axonopodis pv. malvacearum